2016
DOI: 10.4274/mirt.07078
|View full text |Cite
|
Sign up to set email alerts
|

18F-Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography Imaging in a Patient with HIV (-) Kaposi Sarcoma

Abstract: Kaposi sarcoma (KS) is a vascular neoplasm that often manifests with multiple vascular nodules on the skin and other organs. Various imaging modalities can be used to display disease extent. Herein we present a 65-year-old female patient with human immunodeficiency virus negative KS along with her whole-body positron emission tomography/computed tomography imaging findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(11 reference statements)
1
3
0
Order By: Relevance
“…Limited published data are available on the DA of FDG PET/CT in KS. Some case series suggested the efficacy of FDG PET/CT for KS staging, with FDG-avid lesions identified in the skin, lymph nodes, as well as occult visceral locations [17,19,[24][25][26], and for follow-up during treatment [18,27,28]. Our study confirmed some of these preliminary data in a large population.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Limited published data are available on the DA of FDG PET/CT in KS. Some case series suggested the efficacy of FDG PET/CT for KS staging, with FDG-avid lesions identified in the skin, lymph nodes, as well as occult visceral locations [17,19,[24][25][26], and for follow-up during treatment [18,27,28]. Our study confirmed some of these preliminary data in a large population.…”
Section: Discussionsupporting
confidence: 84%
“…FDG PET/CT can provide a whole-body assessment of a proliferative or inflammatory disease, delivering metabolic and morphologic information concomitantly. Some cases of patients with KS successfully assessed with FDG PET/CT were reported, suggesting that it may be a useful tool to assess KS extension or treatment response [17][18][19][20][21][22]. However, no study measuring the efficacy of FDG PET/CT in KS has been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…Skin uptake can be focal or diffuse and is more commonly seen in the legs and lower torso. In addition, it can help distinguish visceral or skeletal involvement [56], which can portend a worse prognosis. KS is a widespread disease that can be occult and can affect essentially every organ; and 18 F-FDG-PET/CT scans can be beneficial for whole-body staging [57] (Fig.…”
Section: Imaging Of Kaposi Sarcoma Using Pet/ctmentioning
confidence: 99%
“…FDG-avid KS lesions have been reported in the skin [ 58 , 59 , 62 , 64 , 67 , 68 , 69 ], lymph nodes [ 59 , 62 , 63 , 64 , 65 , 66 , 67 ], bone [ 61 , 64 , 67 ], lungs [ 59 , 61 , 62 ], gastro-intestinal tract [ 60 ], mouth [ 66 ], thyroid [ 66 ], and salivary glands [ 64 ], which demonstrates the ability of FDG-PET to detect KS lesions in various organs. Interestingly, for some of these authors, FDG-PET was instrumental in detecting unsuspected KS lesions [ 61 , 62 , 66 ].…”
Section: Fdg-petmentioning
confidence: 99%